Pendekatan Pembelajaran untuk Meningkatkan Literasi Digital Siswa - Muh. Wahyudin S. Adam; Anita Wati Tukloy; Riang Julistiana; Imelvia Munu; Ma’rifatul Khiftiyah (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The research findings indicate that both teachers and students predominantly utilize digital literacy in the learning process. The integration of digital tools has proven to be highly motivating, encouraging students to continue learning, pursue academic achievement, and develop greater interest in the learning process, ultimately leading to higher learning satisfaction. Digital literacy serves not merely as a supporting medium but plays a crucial role in fostering students’ intrinsic motivation to learn independently. Interestingly, while students are largely driven by internal motivation, external rewards or recognition still have a significant impact, especially in specific situations where students need additional encouragement or validation of their achievements. Therefore, digital literacy contributes not only to access to learning resources but also to the creation of a motivating learning environment that supports students' academic growth. These findings highlight the importance of integrating digital technology into education as an effective strategy for enhancing student motivation and satisfaction in the current digital era.